PENGARUH PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA KARYAWAN PT. BANK TABUNGAN NEGARA KANTOR CABANG PEKANBARU - Herda Novita Sari; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Career development is a process to increase individual skill in order to archive better career. And job satisfaction shows how far individual feels about the positive or negative of all factors and dimension from their task in their job. The purpose of this research is to understand career development, job satisfaction and examine the influence of career development to employee job satisfaction at the branch office PT. Bank Tabungan Negara Pekanbaru.The methods used in this research is descriptif method and analytical quantitative analysis. The sampling technique used was random sampling with a population of 68 people and the number of samples is 40 respondents. The data measured with Likert scale. And then the data is processes by using SPSS 17 program.The result of this study indicate that the influence of career development on employee job satisfaction at the branch office PT. Bank Tabungan Negara Kantor Cabang Pekanbaru indicate criteria quite well and quite fix.Keywords : Career Development, Employee Job Satisfaction, Branch Office PT. BankTabungan Negara Pekanbaru